DIAGNOSE THE DISEASE ON DIGESTION APPLICATIONS USING HUMAN MICROSOFT VISUAL BASIC 6.0 - Sri Susanti; Marzuki.SKom.MMSI Marzuki.SKom.MMSI (Jurnal Sistem Informasi, 2008)
Any gastrointestinal disease in humans has a different disease in both the symptomsand treatment of complaints suffered by patients, as well as with the explanation adifferent disease, suffered by the patient (a person) is.To find out the initial suspicion of the disease, the author tries to make the applicationDiagnose Disease In Human Digestion using Visual Basic 6.0.Discussion on Application Diagnose Disease In Human Digestion This Divided intofive namely, Making Flowchart, Display Menu, Input and Output Design andDevelopment program with Visual Basic 6.0